Earning Per Share dan Profitabilitas pada Harga Saham Perusahaan Sektor Makanan dan Minuman di Bursa Efek Indonesia - Aula Nurul Ma'rifah; Estelee Elora Akbar (Jurusan Akuntansi Politeknik Negeri Pontianak, 2022)
The development of the company's stock price on the stock exchange is important for investors and companies. Moreover, this is because it can be an indicator that studies investor behavior. The purpose of this study was to determine the effect of earnings per share and return on assets on stock prices. Sampling using purposive sampling so that there are 15 samples of companies (food and beverage sector). The results of the study show that earnings per share have an effect on stock prices and return on assets has no effect on stock prices. The effect of earning per share is because its large value provides a level of prosperity to shareholders so as to provide profit expectations for investors.